Cecil B. DeMille and The Crusades’ Lionheart: An examination of King Richard I’s depiction in The Crusades (1935) and its effects on the public’s perception of him - Weber, Gregory (Kansas State University. Dept. of History, 2013)
Much scholarly work has been done on Cecil B. DeMille and his movies in general, but not much has been done on DeMille’s The Crusades (1935) specifically. This is especially the case with the film’s depiction of King Richard I of England. DeMille developed his own depiction of Richard through his religious upbringings and Harold Lamb’s book The Flame of Islam. DeMille depicts Richard as a masculine, self-centered warrior king, who most importantly to DeMille, changes his ways and finds his faith in God while on the Crusades. Despite DeMille’s influence and directing, this depiction did not fully translate to audiences at the time of the film’s release.
Keywords: Cecil B. DeMille; King Richard I; The Crusades